Evaluation of naphthalenacetic acid in the cutting of the fruit of guanábana (Annona muricata L.) - Añazco Chávez, Joffre Paúl; Celi Sabando, Kristley David (SATHIRI, 2022)
The present study evaluated the application of naphthaleneacetic acid (NAA) in the productive stage of soursop as an alternative to assisted pollination that has been carried out as a recurrent activity in production assurance. Two treatments were performed with three repetitions, where T1 represented manual or assisted pollination and T2 the use of NAA at 2%. In the results of the variables to be measured, it was obtained that after 30 days of application the percentage of fruits set in T1 was 73.33% while in T2 63.33%. In its counterpart, at 45 days the percentage of aborted fruits was measured, in which it was possible to obtain that T1 reached 25.26% of abortions while T2 only 15.30%. In parallel, the diameter of the fruit was also measured at 45 days and it was observed that in the treatment with fewer abortions the diameter was 2,019 cm while in pollination treatment the fruits measured 2,045 cm. It should be noted that the data obtained did not have a statistically significant difference but had a percentage difference. It is recommended to continue with the research using data on a greater number of days to finish with the harvest and an economic analysis. The data obtained in this study will serve as a basis for future research in order to give the community an alternative to the traditional method of soursop production.